The impact of organic links in position auctions with popular versus niche keywords. (11th May 2018) - Arnold, Michael; Darmon, Eric; Penard, Thierry
Abstract: We analyze a game‐theoretic model to explore the impact of organic links (links generated by the search engine algorithm) and popular versus niche keywords on bidding strategies in sponsored link position auctions. In contrast to results in earlier literature, we find that with organic links the firm with the highest value per click does not necessarily win the first sponsored position; it may be optimal for a firm to bid an amount greater than the expected value from a click; and firms may choose not to bid even if they would incur no cost for clicks on the sponsored link.